The Importance of Syntax in Understanding English Sentence Structure: A Library Research - Purnama, Dirza Rizki; Nasywa, Ibtisamah; Ray, Nurul Anisya; Ismahani, Siti (MUDABBIR Journal Research and Education Studies, 2025)
This study discusses the importance of syntax in understanding English sentence structure, particularly for English as a Foreign Language (EFL) learners. This research employed a qualitative descriptive method using a library research approach by reviewing linguistics textbooks and relevant journal articles. The findings indicate that syntax plays a crucial role in organizing sentence elements such as subjects, verbs, objects, phrases, and clauses, and in interpreting meaning accurately. Syntactic knowledge helps learners understand word order, recognize grammatical relationships, and comprehend both simple and complex sentence patterns. Moreover, syntactic awareness supports learners in producing grammatically correct and meaningful sentences in communication. Therefore, mastering syntax is essential for improving learners’ understanding and effective use of English sentence structure.